Satisfaction with an In-House Nasal Foreign Body Removal Manikin: A Randomized Controlled Trial - Pitathawatchai P; Anuntaseree S; Yuenyongviwat V (Medical Devices: Evidence and Research, 2021)
Pittayapon Pitathawatchai,1 Sittichoke Anuntaseree,2 Varah Yuenyongviwat2 1Department of Otolaryngology Head & Neck Surgery, Faculty of Medicine, Prince of Songkla University, Hatyai, Thailand; 2Department of Orthopedics, Faculty of Medicine, Prince of Songkla University, Hatyai, ThailandCorrespondence: Varah YuenyongviwatDepartment of Orthopedics, Faculty of Medicine, Prince of Songkla University, 15 Karnjanavanich Road, Hat Yai, Songkhla, 90110, ThailandEmail varahortho@gmail.comIntroduction: Nasal foreign bodies can lead to life-threatening conditions. Hence, it is a necessity that physicians be well trained in the appropriate procedures for removal of nasal foreign bodies. However, training on real patients is not only unpractical it is also too dangerous, due to risk of foreign body aspiration during the procedure. Therefore, our goal was to construct a manikin, with a specific design, to serve all possible needs for training.Methods: We developed an in-house manikin from 2 materials; these being flexible polyurethane foam and silicone. Silicone, which has elasticity similar to nasal alae, was used to develop the detachable nose and nasal cavity, whilst polyurethane foam, which is light and easy to carry, was used to develop the head. The in-house manikin was compared with a commercial manikin for satisfaction after a nasal foreign body removal procedure was performed in both groups, by 37 physicians, after conducting a randomized controlled trial with a crossover design.Results: The satisfaction scores of the in-house manikin were statistically significantly higher than the satisfaction scores of the commercial manikin for 6 dimensions: proper size, ease of use, ease of maintenance, flexibility of nasal alae relative to actual anatomy, similarity of the nasal cavity relative to actual anatomy and confidence that the manikin can upskill the medical students ability to practice on real patients (p value < 0.05).Conclusion: This in-house nasal foreign body removal manikin design had high satisfaction for training and could be used to develop further nasal foreign body removal manikins in the future.Keywords: manikin, nasal foreign body removal